Regional Heterogeneity in Employment Determinants: Evidence from Indonesia - Franse; Maichal (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study contributes to the literature by examining regional heterogeneity in employment determinants across Indonesia and underscoring the limitations of models relying solely on national aggregates. Research Objectives: This study investigates the differential impacts of foreign direct investment, economic growth, education, and health on employment at the national level and across distinct regional clusters in Indonesia. Research Methods: The study utilizes panel data regression covering 33 Indonesian provinces from 2011 to 2024, categorized into four regional clusters. Fixed- and random-effects models with robust standard errors are applied, with model selection based on formal specification tests. Empirical Results: The findings reveal substantial regional variation regarding the magnitude and statistical significance of employment determinants. While specific variables show significant associations within certain regions, these relationships remain obscured in national aggregate data. Implications: The results indicate that employment dynamics in Indonesia are inherently regional. Policymakers should prioritize regionally calibrated socioeconomic strategies over uniform national policies to effectively support employment expansion. JEL Classification: J21, F21, O15, O47, R11